The Influence Of Price, Promotion, and Awareness On Customer Satisfaction Among Traveloka Users - Darda, Ahmad; Rojikun, Ahmad (SEAN Institute, 2024)
This research aims to determine the influence of price, promotion and brand awareness on customer satisfaction of Traveloka users. The research method used is a quantitative method with a descriptive design. The research was carried out by searching for primary data through questionnaires to respondents using a purposive sampling method, so the sample used was 116 respondents. The analysis used in this research used SPSS 26.0 software. The analysis technique uses multiple linear regression analysis, and hypothesis testing uses the t-test and F-test to test the regression coefficients partially and simultaneously and the coefficient of determination. The research results show a positive and significant influence of the Price variable on Customer Satisfaction, a positive and significant influence of the Promotion variable on Customer Satisfaction, and a positive and significant impact of the Brand Awareness variable on Customer Satisfaction. Likewise, price, promotion, and brand awareness significantly affect Traveloka's customer satisfaction